Resilience: An Evolutionary Approach to Spatial Economic Systems - Aura Reggiani; Thomas de Graaff; Peter Nijkamp (Tinbergen Institute, 2001)
The concept of resilience has received a great deal of attention in the past decades. Starting fromthe first fundamental definitions offered by Holling, Pimms and Perrings in an economic-ecologicalmodeling context, the present paper explores the `evolution' of the resilience concept – as well asrelated different measures – in both a continuous and discrete time setting.From this perspective, the paper explores the relevance of the resilience concept in socio-economic systems, by focussing the attention on the relationships among resilience, transitiondynamics and lock-in effects, in particular in the light of the dynamics of technological innovationdiffusion and adaptive behaviour of firms. In this framework we will describe an empiricalapplication, in which the resilience and dynamics of the West-German labour market will beinvestigated. This empirical illustration is offered by making use of an algorithm constructed fordetecting Lyapunov exponents, so as to classify the resilience among employment sectors in ourcase study.
Keywords: 330; Raumwirtschaftstheorie; Theorie; Nichtlineare dynamische Systeme; Gleichgewicht